"One Hundred False Starts" : l’espace fitzgéraldien ou la quête d’un ailleurs impossible - Pascal Bardet (Anglophonia)
This article examines all the features of Fitzgeraldian space. Francis Scott Fitzgerald’s entire works deal with a major theme in American literature: man’s alienation from his environment. Therefore, the search for his own identity is in keeping with the quest for a place to call home. This process takes him to the four corners of the American continent and to Europe and incites him to try and grasp the true meaning of his surroundings. Unable to settle down somewhere, man is in perpetual quest but the wanderings of his soul forbid the rebirth of his being. In Scott Fitzgerald’s fiction, departures become drifts.This article is, therefore, an invitation to explore the symbolic landscapes of his works and should allow the reader to better perceive the different components of Francis Scott Fitzgerald’s imaginary world and sense of place.